Broken Endodontic Instrument Caused Inferior Alveolar Nerve Paraesthesia: A Case Report. - Selcuk, M. Ozbek; Süleyman, Kaman; Kemal, Ozgur Demiralp (Journal of Dentistry And Oral Implants, 2016)
A healthy 55-year-old man was referred to the Department of Endodontics, Oral and Dental Healthy Hospital, Eskişehir suffering from pain and paraesthesia in the left lower lip and chin.A panoramic radiograph revealed the presence of broken endodontic instrument beyond the apex of the mandibular left third molar. A cone beam computed tomography (CBCT) examination was undertaken, which revealed that the broken instrument was inside the mandibular canal. Damage to the inferior alveolar nerve (IAN) secondary to extrusion of a broken endodontic instrument was diagnosed. Extraction of the tooth was decided and the patient was prescribed with 1 mg/kg/day prednisone 2 times/day, once-daily regimen, and 150 mg/day pregabalin, two doses per day, monitoring the progress with periodic follow-up visits. One month after the incident, the signs and symptoms were gone. The complete resolution of the paraesthesia and the control of pain achieved in the present case suggest that surgical removal of broken endodontic instrument extruded into the mandibular canal with the use of prednisone and pregabalin is a good option in the management of inferior alveolar nerve injury.
Keywords: Broken endodontic instrument; cone beam computed tomography; paraesthesia